The Impact of institutional quality on standard of living - LISTYAGHI, Hutomo Bayu (KDI School, 2015)
Several prominent studies have been conducted to test the causality of institutional quality on income growth. However, income growth only partially captures the living standard. Many economists, including the noble laureate Amartya Sen, proposed Human Development Index (HDI), as a more comprehensive indicator to capture living standard. Therefore, this study aimed to examine the impact of institutional quality on HDI. The study tests the causality of Institutional quality on HDI by using cross-countries data time period 2005-2013. Pooled OLS and Fixed Effect estimation methods are employed in the analysis. The result of this study showed that institutional quality, as indicated by governance and democratic quality are having significance positive impact on HDI. Under the Fixed Effect scenario, 3 years lags governance is employed, and the result show that governance and democratic quality are remain positively significance on HDI.
Thesis(Master) --KDI School:Master of Development Policy,2015